From Nutrition to Aspirations and Self-Efficacy : Gender Bias Over Time Among Children in Four Countries - Dercon, Stefan (Washington, DC: World Bank, 2012)
We use data on children at age 8, 12 and 15 from Young Lives, a cohort study of 12,000 children across Ethiopia, India (Andhra Pradesh), Peru and Vietnam, to document the presence of a gender gap across a wide variety of indicators, including nutrition, education, aspirations, subjective well-being and psychosocial competencies. First, we find that there is considerable heterogeneity across countries, ages and indicators in whether there is any gender bias and whether it is in favour of boys or girls. Second, we find strong evidence of an 'institutionalized' gender bias against girls in education in India and to an extent, Ethiopia; the bias appears to emerge in educational aspirations of parents for their children at age 8, is transmitted to the aspirations of children at 12 and is transformed into gender gaps in test scores related to cognitive achievement at age 15, despite relatively high enrolments. This bias is stronger in rural than in urban India; in rural Peru there is some evidence a pro-male bias in education at age 12 and 15. We also observe lower self-efficacy (as measured by agency) for girls in Ethiopia and India at age 15. Similar patterns exist in Vietnam but in the opposite direction - in favour of girls rather than boys. Evidence in other studies suggests that lower human capital and non-cognitive skills both lead to poorer performance in the labour market, leading to predictions of continuing bias in outcomes for these groups.